1998
DOI: 10.1007/s001470050423
|View full text |Cite
|
Sign up to set email alerts
|

The quality of life in end stage renal disease care

Abstract: The improved prognosis and survival statistics of both renal transplantation and dialysis have focused attention on the quality of life offered by these treatments. Using a standardized questionnaire, we assessed the quality of life of 612 patients undergoing renal replacement therapy at our center. Of these patients, 359 had been transplanted and 253 patients were on dialysis. Concerning the sociodemographic data, only the time on specific treatment was longer in dialysis patients than in transplanted patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2002
2002
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…A shortcoming in the majority of studies was the omission of the response rate or the lack of clarity on it. Three studies reported a response rate <60% (item B) [29,33,35]. Likewise, not one study reported on the reliability of questionnaires or interviews used for measurement of indicators of social participation, mostly employment status (item D).…”
Section: Methodological Qualitymentioning
confidence: 95%
See 3 more Smart Citations
“…A shortcoming in the majority of studies was the omission of the response rate or the lack of clarity on it. Three studies reported a response rate <60% (item B) [29,33,35]. Likewise, not one study reported on the reliability of questionnaires or interviews used for measurement of indicators of social participation, mostly employment status (item D).…”
Section: Methodological Qualitymentioning
confidence: 95%
“…However, six studies did not describe educational level of the study participants (item E) [30,32,36,[38][39][40]. Furthermore, 11 studies provided insufficient information on clinical variables such as comorbidity (presence of diabetes mellitus) [29,34,35,38,40,41], type of donation (cadaveric or living) [29,35,36,41,42] and dialysis before transplantation (item G) [29,31,36,39,40,42,43]. With respect to data presentation one study omitted reporting information on a relevant indicator of social participation (item I) [31].…”
Section: Methodological Qualitymentioning
confidence: 98%
See 2 more Smart Citations
“…Eine Verbesserung der LQ im körperlichen (Anstieg des Karnofsky-Index von 66 auf 88), psychischen und sozialen Bereich zeigte sich in Abhängigkeit von Geschlecht und Alter der Patienten. Männer erreichten im Durchschnitt höhere Werte als Frauen, Patienten über 55 Jahren wiesen im Mittel eine schlechtere LQ auf.In einer neueren deutschen Querschnittstudie verglichen Waiser et al[66] 359 NTX-Patienten mit 235 Hämo-dialysepatienten. Die NTX-Patienten hatten weniger körperliche Beschwerden als die Dialysepatienten, eine bessere Lebenszufriedenheit, ein geringeres Ausmaß an Depressivität und Ängstlich-keit und waren sozial besser integriert.…”
unclassified